Assessment of acute neuromuscular fatigue manifestations and functional performances after heavy resistance exercise - Zarrouk, N.; Mtibaa, K.; Hammouda, O.; Chtourou, H.; Chaabouni, K.; Ayadi-Makni, F.; Rebai, H. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study aimed to assess neuromuscular fatigue after heavy resistance exercise in rugby players. METHODS: Twelve male rugby players performed five sets of knee extension exercise lifting 80% of their one repetition maximum until failure, with 3min of rest in-between. Maximal voluntary contraction (MVC) and surface electromyographic activity from quadriceps muscles, as well as ions (i.e., Na+, K+, and Cl-) and metabolic responses (i.e., blood lactate and ammonia concentrations) were measured before and after exercise. Maximum repetitions performance and both peripheral (RPEp) and overall body (RPEo) rating of perceived exertion were recorded following each set. RESULTS: The number of maximum repetitions decreased significantly across sets (P<0.001). Both RPEp and RPEo increased significantly across sets (P<0.001) with higher RPEp values after each set (P<0.001). Both RPEp (r=-0.98, P<0.01) and RPEo (r=-0.99, P<0.001) were negatively correlated with the changes in the number of maximum repetitions. MVC (P<0.001), root mean square (P<0.05), and neuromuscular efficiency (P<0.01) as well as Na+ (P<0.01), Cl- (P<0.001) and blood concentrations of lactate (P<0.001) and ammonia (P<0.001) increased significantly after the exercise. However, K+ (P<0.001) increased after the resistance exercise. CONCLUSIONS: Heavy resistance exercise affected both objective (i.e., neuromuscular and biochemical parameters) and subjective (i.e., RPE) aspects of neuromuscular fatigue.